Transient analysis on track circuits in crack state - Bin Zhao (MATEC Web of Conferences, 2018)
The transient transformation of track circuit between the normal state and crack state is analyzed. Firstly, the model of crack state of track circuit in the complex frequency domain is established. According to the boundary conditions of crack state of track circuit, the expression of current traveling wave in the receiving end is obtained in complex frequency domain. Based on it, the numerical solution in the time domain is got by FFT&IFFT conjunction with quotient-difference (Q-D) algorithm. Then, the steady state of circuit in normal state is taken as state of zero moment of track circuit, the transient process from normal state transform into crack state is solved. Thirdly, the Electro-Magnetic Transient Program (EMTP) model of crack operation is established to prove that the transient analysis result is correct. It provides a power theoretical basis to distinguish the operation state of track circuit by transient analysis.